The development of transnational policing: past, present and future - McDaniel, John L. M.; Stonard, Karlie E.; Cox, David J. (Routledge frontiers of criminal justice, 2020)
"This book draws together the insights of eminent academics and specialists to present an overview of past and present approaches to transnational policing throughout the Anglophone world. It aims to revitalize the study of transnational policing by showing that past and present developments in this field remain poorly understood, whilst also suggesting future avenues of research. Containing chapters on police history, police accountability, gendered hate crime in an increasingly online world, counter-radicalisation strategies being pursued around the world, internet-facilitated sex trafficking and changes in organised crime, amongst others, the authors adopt revisionist, orthodox and progressive views in order to challenge our understanding and appreciation of developments in transnational policing. All of the chapters in the book use policing models employed within the UK as either their focal point or as a point of comparison so that direct comparisons and contrasts can be examined. The Development of Transnational Policing illustrates distinctive and separate aspects of what remains an undoubtedly complex and dynamic field, but also forms an overview of developments and the dearth of academic research which surround them, in order hopefully to inspire researchers, policy-makers and practitioners alike"